Pengaruh Pembelajaran Akuntansi Keuangan dan Kemampuan Akademis terhadap Perilaku Hedonis Mahasiswa dalam Mengelola Keuangan - Wahyuni Wahyuni; Nerinza Nerinza; Rini Sulistiyanti (Al-Buhuts, 2024)
This research aims to determine the effect of learning Financial Accounting and academic abilities on students' hedonic behavior in managing their finances. The type of data used in this research is quantitative data with data collection using questionnaires. The questionnaire was distributed to 69 Accounting students at Muhammadiyah University of Makassar Class of 2020. The data source used in this research was primary data with research instruments using a Likert scale. The data collected was processed using multiple linear analysis methods with the help of SPSS Version 26. The results of the research show that: (1)  Learning Financial Accounting has a positive, significant effect On hedonic behavior, (2) Academic ability hasn’t effect on behavior. Of 2020 Muhammadiyah Makassar University Accounting students in managing finances.